CLINICAL EFFECTIVENESS OF ONCE-WEEKLY DULAGLUTIDE AS ADD-ON TO SGLT2i IN THAI PATIENTS WITH T2DM: RETROSPECTIVE STUDY IN A REAL- WORLD SETTING - Thewjitcharoen, Yotsapon; Yenseung, Nalin; Chatchomchaun, Waralee; Butadej, Siriwan; Himathongkam, Thep (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Both GLP-1 receptor agonists (GLP-1 RA) and SGLT2 inhibitors (SGLT2i) reduce the risk of cardiovascular and renal complications when included as part of usual care in T2DM patients with established atherosclerotic cardiovascular disease (ASCVD) or multiple risk factors for ASCVD. Dulaglutide is a once-weekly GLP1-RA which became available in Thailand in 2018. This study aimed to show the real-world use of dulaglutide as add-on to SGLT2i among Thai patients with T2D in a specialized tertiary diabetes center. METHODOLOGY This retrospective cohort study included patients who were prescribed with dulaglutide for at least 1 month between 2018 and 2020 at Theptarin Hospital, Bangkok, Thailand. Primary (change in A1C) and secondary (including change in body weight, glycemic and weight-loss target achievement) endpoints were assessed at baseline and at follow-up visit. RESULTS A total of 41 patients (females 51.2%, mean age 56.9±13.4 years, duration of diabetes 15.7 ± 9.0 years, BMI 34.2 ± 5.8 kg/ m2, baseline A1C 8.5 ± 1.7%, SGLT2i-treated 48.8%, insulin- treated 51.2%, established ASCVD 9.8%) were included in the study. During a mean follow-up of 5.7 months after treatment initiation, the overall mean A1C reduction was 0.9% with weight loss of 2.3 kg. The proportion of patients who could achieve A1C < 7.0% increased from 12.5% to 31.4%. Among SGLT2i-treated patients, overall mean A1C reduction when compared with non SGLT2i-treated patients was 1.0 ± 1.3% and 0.8 ± 1.8%, respectively (p=0.716). Body weight reduction in SGLT2i users was -3.0 ± 4.7 kg while for non-SGLT2i users, it was -1.6 ± 3.4 kg (p=0.277). Reported adverse events were consistent with the known safety profile of GLP-1 RA. CONCLUSION In routine clinical practice among Thai patients with T2D, the combination of dulaglutide and SGLT2i was well tolerated and associated with sustained glycemic control and weight loss in a wide range of patients with T2D comparable with what has been observed in randomized clinical trials.